Dysregulated Tfh/B cells and their interactions in neuromyelitis optica spectrum disorder - Wang, Liang; Zhou, Lei; Wang, Zhouzhou; ZhangBao, Jingzi; Huang, Wenjuan; Tan, Hongmei; Fan, Yuxin; Lu, Chuanzhen; Yu, Jian; Wang, Min; Lu, Jiahong; Zhao, Chongbo; et al. (Frontiers in Immunology, 2026)
BackgroundThis study aimed to compare the proportions of circulating follicular helper T (Tfh) and B cell subsets, as well as serum levels of cytokines and chemokines, between patients with neuromyelitis optica spectrum disorder (NMOSD) who are anti-aquaporin-4 antibody (AQP4-ab)–positive and healthy controls, and to investigate the interaction mechanisms between Tfh and B cells.MethodsAQP4-ab–positive NMOSD patients were enrolled during acute attacks and remission phases, along with age- and sex-matched healthy controls. Flow cytometry was used to assess circulating Tfh and B cell subsets. Purified CD19+ B cells were cultured alone or co-cultured with CD4+CXCR5+ Tfh cells for 6 days, with various interventions applied to evaluate alterations in Tfh or B cell phenotypes. Serum and supernatant levels of interleukin (IL)-6, IL-21, CXCL13, and AQP4-ab were measured.ResultsDuring acute attacks, NMOSD patients exhibited significantly higher proportions of total Tfh, ICOS+ Tfh, activated Tfh17, switched memory B cells, double-negative B cells, plasmablasts, and plasma cells, along with elevated serum levels of IL-6, IL-21, and CXCL13. In contrast, the frequencies of activated Tfh1, naive B cells, and transitional regulatory B cell subsets were significantly reduced. Functional assays revealed that Tfh cells promoted B cell proliferation, differentiation, and AQP4-ab production. Conversely, B cell subsets enhanced Tfh cell proliferation, differentiation, and IL-21 secretion; these effects were attenuated by anti-CD20 and anti–interferon-γ (IFN-γ) monoclonal antibodies, but were augmented by anti–IL-10 monoclonal antibody.ConclusionsCirculating Tfh and B cell subsets are dysregulated in AQP4-ab–positive NMOSD, accompanied by increased levels of IL-6, IL-21, and CXCL13. Reciprocal interactions between Tfh and B cells likely contribute to disease pathogenesis.